Faktor-Faktor Yang Mempengaruhi Keinginan Pindah Kerja (turnover/intention to leave) Karyawan Pada Perusahaan Swasta Kabupaten Sukoharjo - Herudiansyah, Gumar, Soepatini, Ph.D, M. Farid Wajdi, Ph.D (2016)
This study aims to determine the effect of career development , compensation and organizational commitment to turnover intention of employees in private companies Sukoharjo district. This research is a quantitative research. The study population were employees of a private company with a type of manufacturing and services within Sukoharjo. The sample is determined by the technique of convenience sampling method, with respondents as many as 100 people. Methods of data collection techniques used are questionnaire (questionnaire). Data analysis method used is multiple linear analysis method. In the research results obtained by using SPSS, showed that the F-test career development, compensation and organizational commitment jointly have a significant influence on employees' desire to move to a private corporation Sukoharjo district. While the results of the t test of variables of Career Development and Organizational Commitment has no significant effect on turnover intention. while the variable compensation significant effect on turnover intention.